Conseqüências da Implementação do Fundo de Manutenção e Desenvolvimento do Ensino Fundamental e Valorização do Magistério nos Municípios de Limeira e Santa Gertrudes-SP - Schuveter, Maria Helena [UNESP]; Adrião, Theresa Maria de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Este artigo tem o objetivo de analisar as conseqüências da implementação do Fundo de Manutenção e Desenvolvimento do Ensino Fundamental e Valorização do Magistério (FUNDEF) na oferta da educação básica nos municípios de Limeira e Santa Gertrudes (SP) no tocante à dinâmica de responsabilidade entre Estado e Municípios e à composição dos gastos em educação, durante os anos de 1996 a 2002. Para tanto, realizou-se levantamento e análise bibliográfica relacionada ao tema e pesquisa documental junto aos órgãos de administração municipal para coleta e análise de dados empíricos. Este trabalho é resultante de um projeto estadual intitulado Acompanhamento da Implantação do Fundef no estado de São Paulo, a ele vincula-se uma pesquisa nacional sobre a Implantação do Fundef em onze estados brasileiros.

The objective of the article is to analyze the consequences that implement of Fund of Maintenance and Development of the Fundamental School and Teaching Valorization (FUNDEF) in the basic education in the municipals of Limeira and Santa Gertrudes concerning the dynamic of responsibility between state and municipalities and to the composition of the educational expenses during the period 1996-2002. To this it a accomplished both survey and bibliographic analysis connected on the subject and documental research next to the administration municipal organs in order to collect and the analyze of empirical datum This paper presents in a result of the state research named in Implementation Accompaniment of Fundef in the state of São Paulo, and bonding national to a research about Fundef implementation in eleven Brazilian states.
Consequences of the implementation of Fund of Maintenance and Development of Fundamental School and Teaching Valorization (FUNDEF) in the basic education in the municipalities of Limeira and Santa Gertrudes - SP
Keywords: Financiamento da Educação; Descentralização; Gestão